1985
DOI: 10.1115/1.3247490
|View full text |Cite
|
Sign up to set email alerts
|

Computer Implementation, Accuracy, and Timing of Radiation View Factor Algorithms

Abstract: The three-dimensional finite-element thermal analysis of enclosure radiation problems requires the calculation of the geometric surface-co-*surface radi ation view factors.The view factors can be calcu lated by either area or line integration algorithms. This paper addresses the implementation, accuracy, and computational time involved in using these algor ithms. Additionally, an algorithm to identify shadowing surfaces and methods to adjust the calculated view factors for increased accuracy are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…The line integral method was found to be advantageous in terms of accuracy and computing time (Sparrow and Cess 1978). In fact, Shapiro (1985) compared the area integral method with the CDIF using Stokes' theorem and concluded that the CDIF was significantly more accurate. The area integral method also requires longer computational times.…”
Section: Methodsmentioning
confidence: 97%
“…The line integral method was found to be advantageous in terms of accuracy and computing time (Sparrow and Cess 1978). In fact, Shapiro (1985) compared the area integral method with the CDIF using Stokes' theorem and concluded that the CDIF was significantly more accurate. The area integral method also requires longer computational times.…”
Section: Methodsmentioning
confidence: 97%
“…For three-dimensional geometries, the computation of view factors remains problematic despite the great number of developed methods [14,15]. A. F. Emery et al [16] compare the methods for complex geometries.…”
Section: View Factors Calculationmentioning
confidence: 98%
“…There are multiple combinations of x and y which satisfy Eq. (9). In this study, in the case of square surface elements, we assume the region to be handled by each emission point (arrival point) as shown in Fig.…”
Section: Definition Of the Initial Energy Of Radiation Heat Fluxmentioning
confidence: 99%
“…As a method of numerical integration, we use the Mitalas-Stephenson [8] or MS method. The MS method has been verified to calculate view factors with higher accuracy than other numerical integration methods [9]. The actual procedure to perform calculations using the MS method is described in a note at the end of this report.…”
Section: Definition Of the Initial Energy Of Radiation Heat Fluxmentioning
confidence: 99%